Plant biodiversity promotes sustainable agriculture directly and via belowground effects. (July 2022) - Cappelli, Seraina L.; Domeignoz-Horta, Luiz A.; Loaiza, Viviana; Laine, Anna-Liisa
Abstract : While the positive relationship between plant biodiversity and ecosystem functioning (BEF) is well established, the extent to which this is mediated via belowground microbial processes is poorly understood. Growing evidence suggests that plant community structure influences soil microbial diversity, which in turn promotes functions desired for sustainable agriculture. Here, we outline the 'plant-directed' and soil microbe-mediated mechanisms expected to promote positive BEF. We identify how this knowledge can be utilized in plant diversification schemes to maximize ecosystem functioning in agroecosystems, which are typically species poor and sensitive to biotic and abiotic stressors. In the face of resource overexploitation and global change, bridging the gaps between biodiversity science and agricultural practices is crucial to meet food security in the Anthropocene. Highlights: Modern agriculture is characterized by monocultures, which rely on external inputs and contribute to greenhouse gas emissions and biodiversity loss. Biodiversity drives ecosystem functions through multiple mechanisms. The importance of plant–soil feedbacks mediated by soil microbial communities in biodiversity–ecosystem functioning (BEF) relationships for agricultural practices is increasingly recognized. BEF research can guide the development of agricultural diversification practices that rely not only on species diversity but on mechanisms stemming from composition and functional traits to enhance both above- and belowground ecosystem functions. We identify how plant diversity may enhance carbon retention in soils via effects on soil microorganisms. Diversification in agriculture requires a fundamental ecological understanding of underlying mechanisms to alleviate trade-offs between desired ecosystem functions and crop yields.